Nonstationarity of the link between the Tropics and the summer East Atlantic pattern - Rieke, Ole; Greatbatch, Richard J.; Gollan, Gereon; Rieke, Ole; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany; Gollan, Gereon; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany (Atmospheric Science Letters, 2021)
A 700‐year pre‐industrial control run with the MPI‐ESM‐LR model is used to investigate the link between the summer East Atlantic (SEA) pattern and the Pacific‐Caribbean rainfall dipole (PCD), a link that has previously been shown using ERA‐Interim reanalysis data. In the model, it is found that the link between the SEA and PCD is present in some multidecadal epochs but not in others. A simple statistical model reproduces this behaviour. In the statistical model, the SEA is represented by a white noise process plus a weak influence from the PCD based on the full 700 years of the model run. The statistical model is relevant to other extratropical modes of variability, for example, the winter North Atlantic Oscillation (NAO), that are weakly influenced by the Tropics. It follows that the link between the Tropics and the winter NAO is likely to undergo modulation on multidecadal time scales, as found in some previous studies. The results suggest that any predictability of the SEA, and by implication the NAO, based on tropical rainfall may not be robust and may, in fact, be modulated on multidecadal time scales, with implications for seasonal and decadal prediction systems. The positive phase of the SEA is associated with warm summers in Europe. The figure shows the running correlation in 51 year windows between the SEA index and the corresponding tropical rainfall index in a long pre‐industrial model run. The link between tropical rainfall and the SEA exists only in some decadal epochs, shown by the green shading, implying that predictability of the SEA based on tropical rainfall can be expected to vary on multidecadal time scales.